Bagaimana Mengembangkan Kemampuan Spasial dalam Pembelajaran Matematika di Sekolah?: Suatu Tinjauan Literatur - S Sudirman; Fiki Alghadari (Pendidikan Matematika STKIP Kusuma Negara, 2020)
Spatial ability is an important one of the abilities for completing many tasks in everyday life successfully. Spatial ability is considered a type of different ability to others. Therefore, there needs a study on how are the characteristics of spatial abilities and to develop in schools. This paper is to reveal the ways are developing spatial abilities in learning mathematics. Based on literature review from some research, at least that there are six ways to develop spatial abilities in learning mathematics, namely: (1) using spatial language in daily interactions; (2) teaching for sketching and drawing; (3) using a suitable game; (4) using a tangram; (5) using video games; and (6) origami and folding paper. Playing video games like Tetris are exercises for spatial relations, mental rotation, spatial orientation, and spatial visualization.